The Role of Public-Private Partnership in The Development of Higher Educational Infrastructure in Uzbekistan - Kadamboyev Behzod; Yuldasheva Oygul (Zien Journals, 2021)
This article examines the significance of Public Private Partnership (PPP) in education. The major focus of the paper is the education system of Uzbekistan. As well as, the article briefly discusses the opportunities of the mechanism to improve education system of Uzbekistan and to solve problems in it
Keywords: State; Private; Partnership; Higher Education; Efficiency; Development; Qualification